Life’s simple 7 and cardiovascular disease risk knowledge in Hong Kong - Lee, Vivian W. Y.; Fong, Felix Y. H.; Cheng, Franco W. T.; Yan, Bryan P. Y. (BMC cardiovascular disorders, 2019)
Background This study aimed at investigating the CV health and CV disease knowledge in terms of LS7 score among 3 age groups in Hong Kong. Methods A cross-sectional multicenter observational study was conducted to observe the CV health and disease risk knowledge in Hong Kong. Elderly subjects were recruited from 15 elderly centers, whereas young adults and the middle-aged were recruited from 6 on-campus health check sessions. Subjects’ demographics, lifestyle behavior and risk knowledge were obtained through questionnaire while their body mass index, random capillary blood glucose, blood cholesterol and blood pressure were measured. LS7 score and risk knowledge score was calculated. Results The LS7 of younger adult, middle-aged and elderly were 10.6 ± 1.3, 9.3 ± 1.9 and 9.7 ± 1.7 respectively. Only 0.6% participants have attained ideal CV health and 35.9% have 5 to 7 ideal CV health metrics. Elderly performed worst in risk knowledge with a score of 8.1 ± 3.3 while young adult and middle-aged were similar (9.6 ± 1.8 and 9.7 ± 1.5). 71% of the participants correctly identified ≥9 components. Logistic regression revealed that subjects aged ≤65 years (OR 2.341, 95% CI 1.779 to 3.080) and with tertiary education (OR 2.031, 95% CI 1.527 to 2.701) were more likely to obtain optimum LS7. No association was found between having optimum LS7 and full knowledge. Conclusion Only few adults in this study population had ideal CV health as defined by AHA. Knowledge has no association but young age and tertiary education has positive association with CV health.